Menelusuri Gagasan Tafsir Tematis Muḥammad Bāqir al-Ṣadr - Lilik Ummi Kaltsum (Refleksi: Jurnal Kajian Agama dan Filsafat, 2012)
The product of thematic tafsīr is not only related to certain themes, but also must be directly linked to the problem of reality. This article presents a figure of thematic tafsīr, in which he puts more emphasis on solving problems of society and not only focuses on the text of the Qur’ān. He is Muḥammad Bāqir al-Ṣadr. In addition, besides his major work on philosophy, Falsafatunā, he is also renowned a reformer in the field of methods of interpretation (tafsīr).DOI: 10.15408/ref.v13i2.897